The prevalence and co-existence of geriatric syndromes in older patients with dementia compared to those without dementia - SOYSAL, PINAR; SOYSAL P.; Smith L. (My University, 2024)
Background: This study aims to compare frequency and coexistence of geriatric syndromes in older patients with dementia to those without dementia. Methods: 1392 patients admitted to geriatric outpatient clinics were evaluated. Evaluations for eleven geriatric syndromes including polypharmacy, malnutrition, fraility, sarcopenia, dysphagia, urinary incontinence, fear of falling, falls, insomnia, excessive daytime sleepiness, and orthostatic hypotension (OH) were carried out in consultation with the patient and the caregiver. Two groups with and without dementia were matched according to age and gender using the propensity score matching method. Results: A total of 738 patients, 369 with dementia and 369 without dementia were included, of whom 70.1% were female and the mean age was 80.5 ± 6.8. Polypharmacy, malnutrition, frailty, sarcopenia, dysphagia, fear of falling, and excessive daytime sleepiness were significantly higher in patients with dementia (p 0.05). The co-existence of 0, 1, 2, 3, 4 and ≥ 5 geriatric syndromes in the same patient was 4.3%, 10.2%, 11.8%, 16.8%, 13.4% and 43.7% in non-dementia patients, respectively; 2.4%, 7.2%, 9.6%, 8.3%, 10.4% and 62.1% in those with dementia, respectively (p < 0.05). Conclusion: The presence and co-existence of geriatric syndromes is common in patients with dementia. These geriatric syndromes should be examined by clinicians and healthcare professionals who work with the demented population, so that more successful management of dementia patients may be achieved.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Geriatri; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Geriatrics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; GERİATRİ ve GERONTOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; GERIATRICS & GERONTOLOGY; Yaşlanma; Geriatri ve Gerontoloji; Aging; Geriatrics and Gerontology; Dementia; Frailty; Geriatric syndromes; Malnutrition; Older adults; Polypharmacy